V2O5 -MoO3 /TiO2 Catalysts for the Selective Catalytic Reduction of NO in Gas Turbine Exhaust Gas with NH3 - Mongkhonsi, Tharathon; Taweesuk, Bussamas (Journal of Advanced Development in Engineering and Science, 2023)
This research presents the development of mixed metal oxide catalysts V2O5 -MoO3 /TiO2 having a fixed amount of V but different amounts of Mo for the selective catalytic reduction (SCR) of NO by NH3 in a low-medium temperature range. The simulated exhaust gas has the same composition as the exhaust gas of a gas turbine power plant having O2 content as high as 15 %vol. The experiments are carried out in the reaction temperature range 100-450°C. The experimental results show that V2O5 -MoO3 /TiO2 catalysts are suitable catalysts in the low-medium reaction temperature range. Water vapour and SO2 inhibit the SCR reaction in the low reaction temperature region but enhance the SCR activity in the high reaction temperature region. In addition, it is found that the calcination temperature affects the activity of the prepared catalysts.